Sabbatical leave report: Spring 2014 - Antonios, Imad (2014)
the page describes the 3 projects Antonios completed: Data Network Traffic Analysis, Gossiping Algorithm Development and Analysis, and ZigBee Networks
Keywords: dept.csc; faculty_collection; sabbatical_report

Asynchronous gossip-based data propagation protocol - Andrew, Priyanka; Antonios, Imad (Institute of Electrical and Electronics Engineers Inc., 2015)
Data dissemination protocols govern interaction and exchange of data among nodes in a distributed system. An understanding of data transfer protocols provides insight into efficient middleware management. Due to their simplicity, scalability and fault-tolerance, gossip-based protocols are researched widely as an effective communication strategy. The Shuffle protocol presented in [1], is an example of a decentralized, gossip-based data transfer protocol used to spread information in a wireless network via probabilistic exchange of data. This paper presents, an asynchronous variant of the Shuffle protocol and a system model that captures variability in data transmission times. This transmission time variability is inherent in dynamic networks, where such algorithms are typically deployed. A simulation-based analysis of the protocol's performance behavior is presented. Results show the effects of transmission variability, on data replication and its coverage. Also examined is the relationship between available storage and the performance of the protocol, expressed using measures such as propagation time and work. © 2015 IEEE.
Keywords: Data communication systems; Data dissemination; Data dissemination protocols; Data propagation protocols; Data transfer; Data transfer protocols; Digital storage; Distributed database systems; Effective communication; Fault tolerance; Fault tolerant computer systems; Gossip-based algorithms; Gossip-based protocol; Internet protocols; Middleware; Shuffle protocol; Simulation-based analysis; Wireless networks; asynchronous gossip-based algorithm; data dissemination; data transfer protocol; dept.csc; wireless network

Understanding the relationship between network traffic correlation and queueing behavior: A review based on the N-Burst ON/OFF model - Schwefel, Hans-Peter; Antonios, Imad; Lipsky, Lester (Performance Evaluation, 2017)
Understanding the impact of network traffic properties on performance behavior in bottleneck links or larger networks is of primary interest to traffic analysts and network designers. Among the contributing factors, variance and correlation properties have been thoroughly studied and a large set of individual results have been obtained. However, these individual contributing factors are not sufficient to predict performance behavior. In this paper we review a unifying and versatile class of ON/OFF models through which the relationship among these parameters can be characterized and their influence on network performance be understood. The analytic performance results from the model show that there is a radically different queueing behavior when the ON period duration follows truncated power-tail distributions (even if truncated), as opposed to model variants where these distribution types are used for the OFF periods. All these models create correlation functions that only decay slowly. This motivates the development of a simple data analysis scheme to distinguish performance relevant correlation. The scheme is described both for interarrival and count processes of traffic data and its effectiveness is shown using real data traces.
Keywords: Contributing factor; Correlation function; Correlation properties; Long range dependence; Long-range dependence; Network designer; Network traffic; ON/OFF models; Power-tail distributions; Queueing model; Queueing models; Queueing networks; Queueing theory; Tail distribution; dept.csc

Impact of time interval alignment on data quality in electricity grids - Schwefel, Hans-Peter; Antonios, Imad; Lipsky, Lester (Institute of Electrical and Electronics Engineers Inc., 2018)
Measurements of parameters in electricity grids are frequently average values over some time interval. In scenarios of distributed measurements such as in distribution grids, offsets of local clocks can result in the averaging interval being misaligned. This paper investigates the properties of the so-called time alignment error of such measurands that is caused by shifts of the averaging interval. A Markov model is derived that allows for numerically calculating the expected value and other distribution properties of this error. Actual consumption measurements of an office building are used to study the behavior of this time alignment error, and to compare the results from the trace with numerical results and simulations from a fitted Markov model. For increasing averaging interval offset, the time alignment error approaches a normal distribution, whose parameters can be calculated or approximated from the Markov model.
Keywords: Alignment; Clocks; Consumption measurement; Data Quality; Data quality; Distributed measurements; Distribution Grid Measurements; Distribution grid; Distribution property; Electric power transmission networks; Errors; Markov Models; Markov model; Markov processes; Mathematical model; Measurement uncertainty; Normal distribution; Numerical models; Numerical results; Office buildings; Power measurement; Smart power grids; Time Alignment Error; Time alignment; actual consumption measurements; averaging interval offset; data quality; dept.csc; distributed measurements; distribution grids; distribution properties; electricity grids; fitted Markov model; normal distribution; parameter measurement; power grids; power supply quality; power system measurement; time alignment error; time interval alignment

A performance model of gossip-based update propagation - Antonios, Imad; Dhar, Reetu; Zhang, Feng; Lipsky, Lester (2010)
We consider the problem of propagating an update to nodes in a distributed system using two gossiping protocols. The first is an idealized algorithm with static and dynamic knowledge of the system, and the second is a simple randomized algorithm. We construct a theoretical model that allows us to derive work and completion time statistics under varying transmission delay distributions. Numerical results are obtained for both exponential and nonexponential transmission times using linear-algebraic queueing theory techniques. Additionally, we present the results of simulation experiments showing that under node churn assumptions, the randomized algorithm's performance is qualitatively different than in a fault-free system. © 2010 IEEE.
Keywords: Algorithms; Completion time; Distributed systems; Gossiping protocols; Linear-algebraic; Numerical results; Performance Model; Queueing theory; Randomized Algorithms; Simulation experiments; Static and dynamic; Theoretical models; Transmission delays; dept.csc